A Case Report of Erythema Multiforme - Md Mohaiminul Islam; Md Huzzatul Islam Khan; Rifat Rahman; Md Ashif Iqbal (Update Dental College, 2019)
Erythema multiforme is a reactive mucocutaneous disorder which is an acute, self-limiting, inflammatory disorder characterized by degrees of blistering and ulceration. This disorder is created hypersensitivity reaction which is triggered by certain infection, medication , food additives or chemicals. We report a case of erythema multiforme managed with prophylactic valacyclovir and systemic corticosteroid. An 47 years old female patients had lesions in the oral cavity, lips, hand and ear which had been diagnosed as erythema multiforme minor. This was not related to drug intake; it was related to food intake. We can treat this disease with valacyclovir for 2weeks to control this disorder. Update Dent. Coll. j: 2019; 9 (2): 46-49